PERAN PEMERINTAH DAERAH DALAM PEMBERDAYAAN USAHA NILAM DI KECAMATAN WATUBANGGA KABUPATEN KOLAKA - Muhammad Askari Zakariah; Dr.H Amir Sahaka; sudarmiati sudarmiati (Jurnal Ekonomi Bisnis Syariah, 2019)
This study aims to determine the role of local government in the empowerment of patchouli business in Watubangga Sub-district, Kolaka District. Data collection methods with in-depth interviews, non-participant observation and documentation. Data were analyzed by qualitative domain approach analysis. The results showed that the role of the Kolaka district government was very important to the survival of the community, among the government's functions in community empowerment was the fulfillment of the needs of patchouli business actors. The impact of patchouli business empowerment greatly affects the survival of Popalia Village because the community's work there is determined by patchouli income itself.